Policing life and death: race, violence, and resistance in Puerto Rico - LeBrón, Marisol (University of California Press, 2019)
"Policing Life and Death : Race, Violence, and Resistance in Puerto Rico examines how policing reinforces social inequality along lines of race, class, gender, and sexuality and analyzes the ways that marginalized populations push against logics and practices of criminalization. Marisol LeBrón traces the rise of punitive governance in Puerto Rico over the course of the twentieth century to the present moment. She argues that Puerto Rican elites and policy makers have turned to policing as a way of reorganizing and strengthening the state in response to deep and ongoing structural crises stemming from the island's incorporation into the United States as a colonial territory. At the same time, LeBrón provides powerful examples of how Puerto Ricans negotiate and resist their subjection to increased levels of segregation, criminalization, discrimination, and violence. Puerto Ricans are actively rejecting punitive solutions and working toward alternative understandings of justice, safety, and accountability"--Provided by publisher